HOLISTIC APPROACH TOWARDS PHYSICAL EDUCATION IN ARCHITECTURE CURRICULUM - Desai, Gayatri; Narkhede, Parag (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The field of Architecture demands immense dedication and commitment. Architecture students undergo significant stress and pressure to complete the workload of the subjects in a dedicated time frame. It is observed that the 1st year students sometimes find it difficult to adjust to this routine and curriculum as it is different from what they have studied in the Higher Secondary Education system. Therefore, it is necessary to familiarize the students with this creative field and also help them cope with stress and time management strategies. Physical education is essential for the physical well-being as well as the mental health of students. The architectural field being spatial Art, it engages body and mind in spaces where one lives, works or plays. The student has continuous interaction with the surroundings and the surrounding affects one’s perception also the satisfaction of one’s living quality. Introducing Physical education to students is a way to help them realize the importance of physical fitness and mental well-being. Physical Education is a curricular component in the F.Y. B.Arch., S.P.P.U. syllabus 2019 pattern; it creates an opportunity to help students explore the importance of ‘Mind and Body’ and its effect on academics. This research paper explores the importance of physical education and mental well-being in achieving academic excellence. Activities along with assignments are curated based on the factors that examine various ways in which physical education can help architecture students develop the skills and knowledge necessary to succeed in the classroom and beyond.